Babesia Species of Domestic Cats: Molecular Characterization Has Opened Pandora's Box - Penzhorn, Barend L.; Oosthuizen, Marinda C. (Frontiers in Veterinary Science, 2020)
This is the first comprehensive review of the literature pertaining to Babesia species reported from domestic cats. Description of the four species (Babesia felis, Babesia cati, Babesia herpailuri, and Babesia pantherae) named based on morphology and/or host specificity is documented. Feline babesiosis is of major veterinary concern only in South Africa. Reports of the rare occurrence of feline babesiosis cases in Europe (France, Germany, Poland, and Spain) and Asia (Israel, India, and Pakistan) are documented. Molecular characterization has revealed that cats can harbor a variety of Babesia species. The previous practice of referring to all piroplasms, especially small ones, seen on feline blood smears as B. felis is therefore no longer tenable. The near-full-length 18S rRNA gene sequences entered into GenBank in 2001 (accession no. AF244912) are designated as definitive for B. felis sensu stricto. All published literature relating to molecular characterization of feline Babesia species that could be traced was critically assessed. Four Babesia species are now known to be involved in causing feline babesiosis in South Africa: the closely related B. felis s.s. and Babesia leo (clade I), Babesia lengau (clade II), and Babesia species cat Western Cape (clade VI, Babesia s.s.). Clade VI also includes Babesia canis presentii and Babesia hongkongensis reported from cats in Asia. Six other Babesia species have been reported from domestic cats: the dog-associated B. canis s.s., Babesia gibsoni, and B. vogeli, as well as Babesia lohae, Babesia microti, and Babesia vulpes. Phylogenetic relationships of all named species were assessed and are presented as trees. The relatively high prevalence of B. vogeli in clinically healthy cats (16% in Brazil, 13% on St Kitts, and 8.1% in Portugal) suggests that immunocompetent cats can harbor the infection with no discernible untoward effects. Reports of occurrence of B. felis and other Babesia species in domestic cats should be accepted only if they are supported by credible molecular provenance.